Development of a Hypercontent-Based E-Module for the Basic Vocational Competencies Subject at SMKS Teknologi Informatika Bulukumba - Ade Alfian; Zulhajji; Alifya NFH (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – This study aimed to develop and evaluate a hypercontent-based e-module for the Basic Skills subject at Bulukumba Informatics Technology Vocational School (SMKS). Methods – The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). The participants were tenth-grade students majoring in Computer Network and Telecommunication Engineering (TJKT). The e-module was evaluated in terms of validity, feasibility, and effectiveness. Validity was assessed by material and media experts using validation sheets, feasibility was measured through student response questionnaires in small- and large-group trials, and effectiveness was determined using pre-test and post-test scores analyzed with the N-Gain method. Findings – The results indicated that the e-module achieved a very high level of validity (98.18% from material experts and 97.50% from media experts), was considered highly feasible by students (91.00% in the small-group trial and 88.57% in the large-group trial), and effectively improved learning outcomes (average N-Gain = 0.85; N-Gain percentage = 85%). These findings indicate that the developed e-module is valid, feasible, and effective for supporting Basic Skills learning. Research implications – However, the study was limited to a single vocational school, and its effectiveness was evaluated only through short-term learning outcomes. Originality – Therefore, further studies involving more diverse educational settings and long-term evaluations are recommended to strengthen the generalizability of the findings.